Pengembangan Media Pembelajaran Interaktif Gerakan Shalat Berbasis AR (Studi Kasus: Madrasah Diniyah Al-Barokah) - Teguh Gumelar; Alun Sujjada; Ivana Lucia Kharisma (Sekawan Institut, 2025)
Fiqh learning in madrasah diniyah often still relies on conventional media such as textbooks, which tend to be less engaging for students and may lead to decreased interest. This study aims to develop an interactive learning media for shalat movements using Augmented Reality (AR) technology and the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). AR was chosen as an innovative solution to deliver fiqh material in a more visual, interactive, and contextual manner. The application was designed using a marker-based approach and visualizes eight shalat movements through 3D animated objects validated by Islamic scholars. The trial was conducted at Madrasah Diniyah Al-Barokah involving 8 students and 2 teachers. Black-box testing confirmed that all features functioned properly across different devices. Meanwhile, the User Acceptance Test (UAT) showed a very high level of user satisfaction, with an average score of 91.22%, particularly in terms of ease of use, visual appeal, and clarity of content. Unlike previous studies, this application specifically focuses on visualizing shalat movements for children in madrasah diniyah within the context of fiqh learning. This research recommends future development with broader user testing and the integration of quantitative learning outcome evaluations.